Stability of electroluminescent perovskite quantum dots light‐emitting diode. Issue 3 (22nd August 2021) - Wen, Zhuoqi; Xie, Fengxian; Choy, Wallace. C. H.
Abstract: Colloidal quantum dots (QDs) are considered to be a promising candidate for light‐emitting diodes (LEDs) applications considering their wide gamut range, simple color tuning, compatibility with large‐size and flexible substrates. Benefiting from the distinguished properties such as high photoluminescence quantum efficiency (PLQY), narrow emission linewidth, and low material cost, perovskite QDs have attracted wide attention from researchers. Despite tremendous progress has been made during the past several years, perovskite QDs‐based LEDs (QLEDs) are still plagued by the instability arising from the operation of the perovskite QLEDs, which have not been studied systematically. In this review, the origin of the instability of perovskite QLEDs is attributed to the vulnerability of emission materials and constituent layers. Simultaneously, the effective strategies to improve the durability of perovskite QDs and QLEDs are summarized, such as component engineering, ligand passivation, fabrication of robust and uniform constituent layers, as well as adopt appropriate device structures and driving modes. Ultimately, we put forward insights on the future research direction and prospects for perovskite QLEDs in practical applications. Abstract : The work described the ways to effective improve the stability of perovskite QLEDs including preparing robust perovskite crystals with low defect density, constructing chemically stable constituent layer with efficient and balanced carrier transport capacity, developing novel device structures, and adopting moderate driving modes.